2004
DOI: 10.1021/es0495157
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Transformation of 3-Bromo-2,2-bis(bromomethyl)propanol under Basic Conditions

Abstract: The mechanism of the spontaneous decomposition of 3-bromo-2,2-bis(bromomethyl)propanol (TBNPA) and the kinetics of the reaction of the parent compound and two subsequent products were determined in aqueous solution at temperatures from 30 to 70 degrees C and pH from 7.0 to 9.5. TBNPA is decomposed by a sequence of reactions that form 3,3-bis(bromomethyl)oxetane (BBMO), 3-bromomethyl-3-hydroxymethyloxetane (BMHMO), and 2,6-dioxaspiro[3.3]-heptane (DOH), releasing one bromide ion at each stage. The pseudo-first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…TBNPA has been reported to be present in ground water in the vicinity of the Negev industrial complex in Israel (Ezra, 2005(Ezra, , 2006. The compound has a relatively strong resistance to biodegradation and therefore classified as not readily biodegradable (0-7 % degradation after 28 days).…”
Section: Sources Use and Environmental Fatementioning
confidence: 99%
See 2 more Smart Citations
“…TBNPA has been reported to be present in ground water in the vicinity of the Negev industrial complex in Israel (Ezra, 2005(Ezra, , 2006. The compound has a relatively strong resistance to biodegradation and therefore classified as not readily biodegradable (0-7 % degradation after 28 days).…”
Section: Sources Use and Environmental Fatementioning
confidence: 99%
“…The mechanism of the spontaneous decomposition of TBNPA) and the kinetics of the reaction of the parent compound and two subsequent degradation products were determined in aqueous solution at temperatures from 30 to 70 °C and pH from 7.0 to 9.5. It was found that TBNPA could be decomposed by a sequence of reactions that form 3,3-bis(bromomethyl)oxetane, 3-bromomethyl-3-hydroxymethyloxetane, and 2,6-dioxaspiro[3.3]-heptane (DOH), releasing one bromide ion at each stage (Ezra et al, 2005). Segev et al (2009) have experimentally confirmed that TBNPA can undergo microbiological degradation and that the process can be facilitated in order to improve treatment of ground water.…”
Section: B R O H B R B Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Tribromoneopentyl-alcohol (TBNPA) is an intermediate for BFRs, and is used as a reactive flame retardant in polyurethanes (Ezra et al, 2005). It is also present as a semivolatile contaminant in the vadose zone beneath an industrial complex in the northern Negev desert,…”
Section: Photodegradation Of Five Individual Pbdementioning
confidence: 99%
“…HBCD was transformed in all biotic samples, and half-lives under anaerobic conditions (ranging from 1.1-6.9 d) were much shorter than those for aerobic conditions (11-63 d) for similar soil or sediment. Although some loss of HBCD was observed in abiotic controls, biotransformation clearly was an important removal mechanism in biotic microcosms.Tribromoneopentyl-alcohol (TBNPA) is an intermediate for BFRs, and is used as a reactive flame retardant in polyurethanes(Ezra et al, 2005). It is also present as a semivolatile contaminant in the vadose zonebeneath an industrial complex in the northern Negev desert, Israel.…”
mentioning
confidence: 99%